The nuclear GYF protein CD2BP2/U5–52K is required for T cell homeostasis - Bertazzon, Miriam; Hurtado-Pico, Almudena; Plaza-Sirvent, Carlos; Schuster, Marc; Preußner, Marco; Kuropka, Benno; Liu, Fan; Kirsten, Andor Zenon Amandus; Schmitt, Xiao Jakob; König, Benjamin; Álvaro-Benito, Miguel; Abualrous, Esam T.; et al. (Frontiers in Immunology, 2024)
The question whether interference with the ubiquitous splicing machinery can lead to cell-type specific perturbation of cellular function is addressed here by T cell specific ablation of the general U5 snRNP assembly factor CD2BP2/U5–52K. This protein defines the family of nuclear GYF domain containing proteins that are ubiquitously expressed in eukaryotes with essential functions ascribed to early embryogenesis and organ function. Abrogating CD2BP2/U5–52K in T cells, allows us to delineate the consequences of splicing machinery interferences for T cell development and function. Increased T cell lymphopenia and T cell death are observed upon depletion of CD2BP2/U5–52K. A substantial increase in exon skipping coincides with the observed defect in the proliferation/differentiation balance in the absence of CD2BP2/U5–52K. Prominently, skipping of exon 7 in Mdm4 is observed, coinciding with upregulation of pro-apoptotic gene expression profiles upon CD2BP2/U5–52K depletion. Furthermore, we observe enhanced sensitivity of naïve T cells compared to memory T cells to changes in CD2BP2/U5–52K levels, indicating that depletion of this general splicing factor leads to modulation of T cell homeostasis. Given the recent structural characterization of the U5 snRNP and the crosslinking mass spectrometry data given here, design of inhibitors of the U5 snRNP conceivably offers new ways to manipulate T cell function in settings of disease.